Stationary leakage from a gravity sewer into horizontal unsaturated-saturated soil – a numerical benchmark for the verification of pipe leakage models. Issue 6 (3rd July 2021) - Peche, Aaron; Graf, Thomas
ABSTRACT: Pipe leakage from defect subsurface gravity sewer pipe networks potentially contaminates soil and groundwater. In recent times, an increasing number of numerical pipe leakage models incorporating pipe flow, saturated-unsaturated flow in the subsurface, and exchange fluxes from and to leaky pipes have been developed. Numerical benchmarks are required in order to demonstrate result accuracy of these models. The present technical note represents a novel numerical benchmark of the pipe leakage problem describing pipe water exfiltration into horizontal unsaturated-saturated soil. The present benchmark enables to test the accurate calculation of the spatial potential distribution in the soil, which is affected by the water level in the leaky pipe. The derivation of an analytical solution for stationary pipe water exfiltration into a horizontal aquifer and a conceptual model for the setup of a corresponding numerical model is shown. Results of the analytical model are reproduced using the numerical leakage model OGS-HE.